Multi-Objective Faculty Course Assignment Problem Based on the Double Parametric Form of Fuzzy Preferences - Sunil, B. Bhoi; Jayesh, M. Dhodiya (Operations Research and Decisions)
This paper presents a mathematical model of the multi-objective faculty course assignment problem based on the double parametric form of fuzzy preferences. The fuzzy preferences are based on an analysis of faculty feedback given by students and an analysis of the results of the previous year's examination of students. The proposed model is developed utilizing faculty members' preferences, the preferences of an administrator for faculty members to courses, and fuzzy preferences based on faculty feedback and student result analysis. The double parametric approach solves a timetabling problem based on information from a university's hypothetical numerical data. The fuzzy programming technique with linear membership function is applied to generate efficient and non-dominated allocations with better optimal values and degree of satisfaction of objective functions for different values of parameters α and β for fuzzy preferences. Results are found using LINGO19.0 software. (original abstract)